Justify your alpha - Lakens, Daniel; Adolfi, Federico G.; Albers, Casper J.; Anvari, Farid; Apps, Matthew A.J.; Argamon, Shlomo E.; Baguley, Thom; Becker, Raymond B.; Benning, Stephen D.; Bradford, Daniel E.; Buchanan, Erin M.; Caldwell, Aaron R.; et al. (Nature Publishing Group, 2018)
In response to recommendations to redefine statistical significance to p ≤ .005, we propose that researchers should transparently report and justify all choices they make when designing a study, including the alpha level.